FYP student selection and examiner allocation system part 2 - Tan, Zheng Kai (Nanyang Technological University, 2024)
As part of the Computer Science curriculum, students in their final year of study in Nanyang Technological University must take up a Final Year Project (FYP) to fulfill the degree’s requirement. The inclusion of the FYP aims to provide a platform for students to apply their theoretical knowledge into practical activities, allowing them to understand the relevance of their education and prepare for their future careers. The Final Year Project allocation system involves 2 interconnected systems: the Student Selection System (SSS) and the Final Year Project Examiner Allocation System (FEAS). At the beginning of each semester, students who are obligated to undertake their FYP will select up to 15 projects from a comprehensive list provided by professors, ranking their project selections based on their own preferences. With the large number of students selecting their project preferences each semester and having to take every student’s preference into consideration, it is extremely challenging to manually assign students to projects. Hence, the 2 systems were developed with algorithms to automate the allocation process and ensure fairness and efficiency. This automated approach proves to be more reliable and accurate compared to manual assignment, minimizing the risk of human error. Each successive cohort of students undertaking this project for their Final Year Project (FYP) has been responsible for the upkeep and enhancement of the FEAS and SSS systems. They will then pass down these responsibilities to the following batch of FYP students to ensure the system operates as intended. The objective of this FYP project is to sustain the ongoing maintenance of the project while incorporating potential enhancements to the system, thereby enhancing its overall efficiency.